Putting bicarbonate on the spot: pharmacological insights for CFTR correction in the airway epithelium - Zajac, Miroslaw; Lepissier, Agathe; Dréano, Elise; Chevalier, Benoit; Hatton, Aurélie; Kelly-Aubert, Mairead; Guidone, Daniela; Planelles, Gabrielle; Edelman, Aleksander; Girodon, Emmanuelle; Hinzpeter, Alexandre; Crambert, Gilles; et al. (Frontiers in Pharmacology, 2023)
Cystic fibrosis (CF) is caused by defective Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) protein. CFTR controls chloride (Cl -) and bicarbonate (HCO3 -) transport into the Airway Surface Liquid (ASL). We investigated the impact of F508del-CFTR correction on HCO3 -secretion by studying transepithelial HCO3 -fluxes. HCO3 -secretion was measured by pH-stat technique in primary human respiratory epithelial cells from healthy subjects (WT) and people with CF (pwCF) carrying at least one F508del variant. Its changes after CFTR modulation by the triple combination VX445/661/770 and in the context of TNF-α+IL-17 induced inflammation were correlated to ASL pH and transcriptional levels of CFTR and other HCO3 - transporters of airway epithelia such as SLC26A4 (Pendrin), SLC26A9 and NBCe1. CFTR-mediated HCO3 -secretion was not detected in F508del primary human respiratory epithelial cells. It was rescued up to ~ 80% of the WT level by VX-445/661/770. In contrast, TNF-α+IL-17 normalized transepithelial HCO3 -transport and increased ASLpH. This was related to an increase in SLC26A4 and CFTR transcript levels. VX-445/661/770 induced an increase in pH only in the context of inflammation. Effects on HCO3 -transport were not different between F508del homozygous and F508del compound heterozygous CF airway epithelia. Our studies show that correction of F508del-CFTR HCO3 -is not sufficient to buffer acidic ASL and that inflammation is a key regulator of HCO3 -secretion in CF airways. Prediction of the response to CFTR modulators by theratyping should take into account airway inflammation.